Wooden Badge Scouting Team Leaders’ Performance Evaluation in Iraq - هيثم صالح, صالح; إبراهيم سهيل, سؤدد (Journal of Physical Education, 2020)
The research aimed at evaluating scouting team leaders who have the wooden badge in Iraq by identifying the reality of their performance. The problem of the research lies in the lack of studies and researchers that evaluate scouting team leaders who have a wooden badge in Iraq. The researchers used the descriptive method on (215) scouting team leaders in Iraq divided into (24) pilot study subjects, and (191) evaluation subjects. They also used questionnaires that consisted of six fields (administrative, leadership, cognitive, skill, communication, and physiological) distributed on (5) items. The data was collected and treated using SPSS to come up with the conclusions and recommendations.